If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2(3 + -2x) = -4(3 + -1x) 6 + (3 * -2 + -2x * -2) = -4(3 + -1x) 6 + (-6 + 4x) = -4(3 + -1x) Combine like terms: 6 + -6 = 0 0 + 4x = -4(3 + -1x) 4x = -4(3 + -1x) 4x = (3 * -4 + -1x * -4) 4x = (-12 + 4x) Add '-4x' to each side of the equation. 4x + -4x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 0 = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 0 = -12 + 0 0 = -12 Solving 0 = -12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -5d=10 | | z-4(z+2)=3(z-4)-2z | | 4(x+2)=14+-2(3+4x) | | -2(6-3x)=-12+6x | | 2m^2+15m+25=0 | | -5d=19 | | 4a-5=29-3 | | 4(9x+2)-5(3+4x)=0 | | -6+k=18 | | 14x-48=x^2 | | 6(x-3)+10=6x-8 | | 3/2-6+5/2=4t+2 | | 3x+5=7+3x-9 | | 5+1.5(z+2)=3.5z-6 | | 2r^2-r-5.25=0 | | 6+-3(6)= | | b^2+8b=-16 | | 475x+25=725 | | 3x+5=7+3y-9 | | b^2+8b=16 | | W-12=-4 | | 5x(2x-1)(5x+7)=0 | | b-6=-3 | | 5n(n+2)=10 | | 8(4-2x)=12-16x | | 2(2x-3)-5(1x+1)=x-4 | | a(a-9)(a-8)=0 | | 6(2q-1)=2q+8q | | N+3.4=5.6 | | n/5+3-10=30 | | a(bx-2)=cx+6 | | 6(4.5y)-12=9 |